The effect of niobium and homogenization on the wear resistance and some mechanical properties of ferritic stainless steel containing 17-18 wt.% chromium - Aksoy, M; Kuzucu, V; Korkut, MH; Yildirim, MM (Elsevier Science Sa, 1999)
The effect of niobium (Nb) content and homogenization on the abrasive wear resistance, surface hardness, microhardness and toughness of ferritic stainless steels containing 17-18 wt.% Cr was investigated. Abrasive wear resistance was related to surface hardness, microhardness and toughness. It was seen that there is approximately a linear relationship between the wear resistance and microhardness of both homogenized and unhomogenized samples: the harder the sample, the more resistant it is to abrasive wear. A similar linear relationship between the wear resistance and surface hardness of the homogenized samples was also seen, but a deviation from this linear relationship occurred between the wear resistance and surface hardness of the unhomogenized samples. In addition, it was also found that the resistance to abrasive wear decreases with increasing toughness of the sample. It was concluded that Nb has no a significant effect on abrasion resistance and toughness for the unhomogenized samples. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: ferritic stainless steel; wear resistance; surface hardness; microhardness; toughness